2018
DOI: 10.1111/anae.14330
|View full text |Cite
|
Sign up to set email alerts
|

The ability of a real‐time injection pressure monitoring system to discriminate between perineural and intraneural injection of the sciatic nerve in fresh cadavers

Abstract: Injection pressure monitoring provides valuable information to prevent intraneural injections and possibly consequent nerve damage during peripheral nerve block. However, the measurement of injection pressure along the injection line is inaccurate as it is influenced by several variables. The aim of this study was to test a new system for precise injection pressure monitoring at the needle tip in a cadaveric model. The system consists of a miniaturised pressure sensor embedded within the needle shaft that is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…8 We have already shown that the system is independent from the injection parameters 9 and that it is able to distinguish between an intraneural and a perineural injection in a cadaver model. 18 In the present study we have shown that the system is able to detect not only an intraneural but also an intravascular injection at a very early stage, distinguishing them from a perineural injection.…”
Section: F I G U R Esupporting
confidence: 52%
“…8 We have already shown that the system is independent from the injection parameters 9 and that it is able to distinguish between an intraneural and a perineural injection in a cadaver model. 18 In the present study we have shown that the system is able to detect not only an intraneural but also an intravascular injection at a very early stage, distinguishing them from a perineural injection.…”
Section: F I G U R Esupporting
confidence: 52%
“…Even though this is used as a training tool in ultrasound‐guided procedures, it has physical properties that differ from human tissues. However, the study of pressure profiles occurring at the needle tip in specific tissues was not the purpose of this study, and has been investigated in a previous cadaveric study . We also used only one needle type and size and studied only three rates of injection, all of which may be different in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The most important conclusion from a clinical viewpoint was that “ injection pressure values measured in the injection line cannot be assumed to be a reliable indicator of the injection pressure at the needle tip ”. In a second experiment, the authors demonstrated that in cadavers, their system was able to discriminate, based on injection pressure, between perineural and intraneural sciatic nerve injections . In the third experiment published this month, the authors demonstrate in keeping with the physical laws of fluid mechanics, that under different injection conditions, the pressure measured in‐line was greater than that measured at the needle tip.…”
Section: What Is New?mentioning
confidence: 92%
“…In past issues and this issue of Anaesthesia , a group of Swiss and French colleagues share with us their findings following a series of in‐vitro and ex‐vivo investigations on injection pressure measurement in needles and injection assemblies used for peripheral regional anaesthesia. The authors first described and validated a novel system for real‐time continuous monitoring of injection pressure at the needle tip using an optical fibre pressure sensor, as compared with conventional in‐line monitors .…”
Section: What Is New?mentioning
confidence: 99%